Chondroitin sulfate-polydopamine modified polyethylene terephthalate with extracellular matrix-mimetic immunoregulatory functions for osseointegration. Issue 48 (21st November 2019) - Li, Ya-Min; Wu, Jing-Yao; Jiang, Jia; Dong, Shi-Kui; Chen, Yun-Su; He, Hong-Yan; Liu, Chang-Sheng; Zhao, Jin-Zhong
Abstract : Optimal integration between the polyethylene terephthalate (PET) graft and host bone is a prerequisite to obtain a satisfactory outcome after graft implantation for ligament reconstruction. Abstract : Optimal integration between the polyethylene terephthalate (PET) graft and host bone is a prerequisite to obtain a satisfactory outcome after graft implantation for ligament reconstruction. Recent studies indicate that complex biosignals including immunoregulation, cell recruitment, and osteogenic differentiation provided by the extracellular matrix (ECM) are conducive to promoting osseointegration. In the present study, a chondroitin sulfate (CS)/polydopamine-modified PET graft was developed to regulate the local immune microenvironment, guide stem cell behavior, and promote new bone formation. We found that CS-modified PET grafts significantly regulated the macrophage phenotype switching from M1 to M2 and promoted the expression of pro-repair cytokines including interleukin (IL)-4, IL-10 and transforming growth factor (TGF)-β1. Moreover, the immunoregulatory function of CS-modified PET guided stem cell behaviors, including recruitment, adhesion, and proliferation, and enhanced the osteogenic differentiation of stem cells. In vivo experiments confirmed that CS-modified PET switched the local immune microenvironment status from pro-inflammatory to anti-inflammatory, up-regulated osteogenic marker expression, and promoted the bone regeneration process, so as to achieve graft-bone osseointegration. These results indicate that an ECM-biomimetic immunoregulatory coating is an effective approach to promote graft integration. This study proposes an effective strategy for an artificial graft to achieve graft-bone osseointegration through immunoregulatory osteogenesis.